EXTERNAL ENVIRONMENT OF REALIZATION OF ENTREPRENEURIAL POTENTIAL OF ENTERPRISE - KHACHATRYAN, VALENTYNA (Herald of Khmelnytskyi National University. Economic sciences, 2021)
The article examines the external environment for the realization of the entrepreneurial potential of the enterprise. Factors influencing the external environment, which include relations with business partners, competition of entrepreneurs, relations with government agencies, relations with tax authorities, relations with the media, relations with financial authorities, investors, socio-demographic, cultural, political, scientific -technological, economic and legal factors. It is proposed to divide all the selected factors into two groups depending on the method of influencing the realization of entrepreneurial potential, in particular to identify factors of direct influence that directly affect the level and degree of effectiveness of entrepreneurial potential and factors of indirect influence - factors that mostly do not risk, but contribute to its change. The peculiarities of the influence of each selected factor substantiated. According to the level of influence on the stability of the production system, it is proposed to distinguish the following groups of environmental factors: external socio-political conditions (changes in the political system); geographical factors (remoteness of markets, increasing the gap between the loads on the management system and its capabilities); industry factors (strategic surprises, loss of control over the external environment of the enterprise, the influence of society and political forces on the market behavior of the enterprise, limited growth, limited resources); personnel factors (changes in human resources in the labor market, the emergence of new methods of justification and strategic decision-making). The most common driving forces influencing entrepreneurial potential proposed, which include changes in long-term trends in economic growth, changes in consumer composition and product use, product updates, technological changes, marketing innovations, changes in public policy and economic regulation, entry into industry or exit from it of large enterprises.
Keywords: entrepreneurial potential; market potential; production potential; strategic potential